DESCRIPTION OF STUDENTS' COUPLING MECHANISM IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC AT SMP N 1 SIEMPAT NEMPU BUNTURAJA IN 2021 - Janwar Gomgom Sinaga (Sean Institute, 2022)
Introduction : Coping mechanism is a pattern to withstand the tension that threatens him (maladaptive self defense) or to solve the problems faced (adaptive coping mechanisms), while online learning is a learning activity by utilizing the internet network, local area network as a method of learning. Problems in online learning faced by students will greatly affect the response of students coping mechanism. Method : The research method used was descriptive, the sampling technique used simple random sampling totaling 78 respondents. Result : The results showed that the male gender was higher in the use of adaptive coping mechanism as many as 32 respondents (41.0%), female sex was higher in the use of adaptive coping mechanism as many as 45 respondents (57.7%), and student coping mechanism in SMP N 1 Siempat Nempu Bunturaja using adaptive coping as many as 78 respondents (100%), and the use of maladaptive coping mechanisms in students at SMP N 1 Siempat Nempu Bunturaja as many as 52 respondents (66.75%). Duscussion : it can be concluded that in online learning during the Covid-19 pandemic, students used more adaptive coping mechanisms.